A Fully Transparent, Stretchable Multi‐Layered Water Barrier Thin Film for the Passivation of Underwater Device Applications. Issue 27 (28th August 2022) - Oh, Myung Seok; Ryu, Jin; Jeon, Mingyu; Lee, Injun; Bae, Byeong‐Soo; You, Jae Bem; Im, Sung Gap
Abstract: Recent developments in wearable and embeddable electronic devices in physiological condition, such as neuroprobe and electroceuticals, have brought forth the need for a reliable passivation layer against water permeation into the devices. On top of the excellent waterproof barrier performance, the passivation layers must also be equipped with stretchability and dermatoid softness for the reliable operation of the devices without failure in the wet environment. Here, this work demonstrates a stretchable, superhydrophobic coating with excellent water barrier performance. The stretchable water barrier coating is formed by depositing alternating layers of a highly stretchable, superhydrophobic copolymer and a crosslinked organosiloxane polymer via initiated chemical vapor deposition. During the deposition, the organosiloxane polymer penetrates into the free volume of superhydrophobic copolymer to form a highly mixed network at the interface. Accordingly, a five‐layered coating shows excellent water and molecular barrier performance with no sign of degradation even at 60% of tensile strain. Moreover, this barrier film formed by vapor deposition is uniformly deposited on the substrate surface regardless of the type and morphology of the substrate. The highly stretchable water barrier coating developed in this study will serve as a promising candidate material for the passivation of various stretchable device applications. Abstract : A stretchable water barrier is formed by depositing alternating layers of a stretchable, superhydrophobic copolymer and a crosslinked organosiloxane polymer via vapor phase deposition. The organosiloxane polymer penetrates into superhydrophobic copolymer during the deposition to form a mixed network at the interface. The barrier coating shows excellent water and molecular barrier performance without degradation even at 60% of tensile strain.